Green Synthesis of Zirconia (ZrO2) Nanoparticles using Curcuma Longa Extract and Investigation of Compressive Strength of Epoxy resin (EP)/ZrO2 Nanocomposites - Bishwokarma, Manish; Bhujel, Arun; Baskota, Manish; Pandit, Rajesh (Journal of Nepal Chemical Society, 2021)
Zirconia (ZrO2) nanoparticles are polymorphic materials having a wide range of applications. It can be synthesized via green as well as chemical synthesis methods. In this work, ZrO2 nanoparticles were synthesized by the green method using Curcuma longa extract. Curcuma longa extract was prepared using the standard method. The synthesized ZrO2 was characterized by the X-ray diffraction (XRD) analysis and Fourier transform infra-red (FTIR) spectroscopy for their structural and size analysis. The analysis of the XRD pattern of ZrO2 showed the tetragonal phase structure and the size was calculated using the Debye Scherrer equation which was about 34.55 nm. The FTIR spectra analysis showed a broad absorption peak particularly at about 774 cm-1 and about 499 cm-1 correspondings to Zr-O2-Zr asymmetric and Zr-O stretching modes, respectively. The characterized ZrO2 nanoparticles were used for the preparation of epoxy resin/ZrO2 nanocomposites. The compressive strength of pure epoxy resin and epoxy resin/ZrO2 nanocomposites were measured by a compressive strength tester and the result indicates the high amount of zirconia was not suitable for the nanocomposites.